2021
DOI: 10.35671/probisnis.v14i2.1258
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Gaya Kepemimpinan, Praktek Manajemen SDM Terhadap Kepercayaan Pada Organisasi Dan Kepuasan Kerja Karyawan Universitas Amikom Purwokerto

Abstract: Memiliki sumber daya manusia yang kompeten, berkarakter dan loyal merupakan bukti efektifitas kegiatan pemanfaatan sumber daya manusia yang berhasil dalam organisasi manajemen. Seorang pemimpin yang tidak memiliki keterampilan untuk menjaga kinerja dan kepuasan kerja adalah pemimpin yang tidak mempercayai bawahannya sesuai dengan peraturan yang berlaku. Tujuan dari penelitian untuk mengetahui pengaruh langsung gaya kepemimpinan dan praktik manajemen sumber daya manusia terhadap kepercayaan organisasi dan kepua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
2
2
0
Order By: Relevance
“…The findings from this study conclude that student satisfaction has a positive and significant influence on student loyalty. This is in line with the results of research conducted by Dharsono, et al (2015), Hariawan (2015), Nasib & Amelia (2018), Sugianto (2016), andRahmawaty (2015) show that student satisfaction has a positive and significant effect on student loyalty. However, contrary to the results of research conducted by Rahmat (2013) found that satisfaction has no effect on loyalty.…”
Section: The Effect Of Facilities On Student Satisfactionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings from this study conclude that student satisfaction has a positive and significant influence on student loyalty. This is in line with the results of research conducted by Dharsono, et al (2015), Hariawan (2015), Nasib & Amelia (2018), Sugianto (2016), andRahmawaty (2015) show that student satisfaction has a positive and significant effect on student loyalty. However, contrary to the results of research conducted by Rahmat (2013) found that satisfaction has no effect on loyalty.…”
Section: The Effect Of Facilities On Student Satisfactionsupporting
confidence: 90%
“…After students feel satisfied with what has been given by the tertiary institution, student loyalty will be created. This is supported by research results from Dharsono, et al (2015), Hariawan (2015), Nasib & Amelia (2018), Sugianto (2016), and Rahmawaty (2015) show that student satisfaction has a positive and significant effect on student loyalty. However, contrary to the results of research conducted by Yulia (2016) found that consumer satisfaction has no significant effect on customer loyalty.…”
Section: Introductionsupporting
confidence: 54%
“…Motivation can be defined as the internal state of individuals who bear power, excitement and dynamics as well as behavior that is directly directed (Shofwa, 2013). Spiritual needs are pure needs whose fulfillment depends on the perfection and maturity of the individual human being.…”
Section: Motivationmentioning
confidence: 99%
“…Spiritual needs are pure needs whose fulfillment depends on the perfection and maturity of the individual human being. (Shofwa, 2013) said that spiritual motivation can improve employee performance. Frederick Herzberg in (Andriani & Widiawati, 2017) put forward a theory of motivation based on the theory of two factors, namely hygiene factors and motivators.…”
Section: Motivationmentioning
confidence: 99%